Kinetically Inert Lanthanide Complexes as Reporter Groups for Binding of Potassium by 18-crown-6 - Junker, A; Tropiano, M; Faulkner, S; Sørensen, T (American Chemical Society, 2016)
The barcode-like spectrum of lanthanide-centered emission has been used in imaging and to make responsive luminescent reporters. The intensities and the shapes of each line in the luminescence spectrum can also report on the coordination environment of the lanthanide ion. Here, we used lanthanide-centered emission to report on the binding of potassium in an 18-crown-6 binding pocket. The responsive systems were made by linking a crown ether to a kinetically inert lanthanide binding pocket using a molecular building block approach. Specifically, an alkyne-appended Ln.DO3A was used as a building block in a copper(I)-catalyzed alkyne-azide cycloaddition (CuAAC) "click" reaction with azide-functionalized crown ethers. The resulting complexes were investigated using NMR and optical methods. Titrations with potassium chloride in methanol observing the sensititzed europium- and terbium-centered emissions were used to investigate the response of the systems. The molecular reporters based on aliphatic crown ethers were found to have strongly inhibited binding of potassium, while the benzo-18-crown-6 derived systems had essentially the same association constants as the native crown ethers. The shape of the lanthanide emission spectra was shown to be unperturbed by the binding of potassium, while the binding was reported by an overall increased intensity of the lanthanide-centered emission. This observation was contrasted to the change in spectral shape between propargyl-Ln.DO3A and the triazolyl-Ln.DO3A complexes. The solution structure of the lanthanide complexes was found to be determining for the observed physical chemical properties of these systems.